Pemanfaatan Limbah Plastik Jenis LDPE (Low Density Polyethylene) Sebagai Tambahan Pembuatan Paving Block Untuk Mengurangi Timbulan Sampah Di TPST Bantargebang - Dodit Ardiatma; Agus Riyadi; Affin Pratama (Prosiding Sains dan Teknologi, 2022)
According to the DKI Jakarta Provincial Environment Agency, in 2016 the average waste entering the Bantargebang TPST reached 6,562 tons/day. The composition of the waste consists of 54% organic waste, 15% paper waste, 14% plastic waste, and others reaching 17% (DKI Jakarta Provincial Environmental Service, 2018). LDPE plastic is a waste that cannot be decomposed by the soil so that its presence in the environment becomes a pollutant. One of the uses of LDPE plastic waste is to change its shape into coarse aggregate for the manufacture of paving blocks. The use of plastic waste is also expected to be able to overcome the problem of using single-use plastics in Indonesia. Quantitative methods in this study were used to determine the quality produced from the process of making paving blocks based on quality standards for compressive strength of paving blocks according to SNI 03-0691-1996. The composition ratios used in this study were 0%, 10%, 20% and 30%. Then the compressive strength and flexural strength were tested for each paving block composition. Based on the results of Mexindo's structural and material laboratory tests. Paving with a mixture of 30% plastic with 28 days of age had good results, namely 26.54 MPa, while paving with a mixture of 10% and 20% plastic had smaller yields of 10.21 Mpa and 8.84 Mpa, but based on SNI on concrete bricks, paving with The plastic aggregate mixture is included in the quality category C. For this flexural strength test, the researcher only compares paving without plastic and paving with plastic mixture, because there is no SNI for the flexural strength of paving. Based on the results of the LDPE Plastic test, aggregates can be made. The results of the compressive strength test of paving with a plastic mixture have good results and enter category C according to SNI. For flexural strength with a mixture of plastics, the results are quite good and are equivalent to those on the market. Based on the quality requirements above, all paving blocks have not passed the test because they have not fulfilled part of the test, namely the water absorption test. Keywords: Waste LDPE, Compressive Strength, and Flexural Strength